Peran Guru PAI dalam Meningkatkan Motivasi Siswa Pada Pembelajaran Membaca dan Menulis Al-Quran - Irvi Reisa; Wasehudin Wasehudin; Irfan Anshori (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
This study aims to find out how the pattern given by Islamic Religious Education Teachers in motivating students to learn to read and write the Qur'an before the learning process began. The scope of this research includes the teacher's role in motivating students and supporting and inhibiting factors in reading and writing the Qur'an. This research uses field research with a descriptive method. Data collection techniques in this study were carried out utilizing observation, interviews, and documentation in the field. This research was conducted at SMP Negeri 14 Serang City. Implementing the habit of reading and writing the Qur'an at SMP Negeri 14 Serang City is going well. This can be seen in the students who are accustomed to and enthusiastic about participating in this activity. This activity routine lasts for 15 minutes, right before class starts. In practice, the activities of reading and writing al-Qur'an are guided directly under the guidance of Islamic religious education teachers. Thus, the teacher can provide direction, guidance, and motivation to students after the process of this activity ends. Supporting factors in this activity include parental support and adequate infrastructure. The inhibiting factor for the covid-19 pandemic, being daring to learn is not conducive to carrying out this Qur'an literacy activity.